Writing Musical Theater - Cohen, A. author. aut Link
XIII, 290 p.
Keywords: This guide to the modern musical covers the entire process of creating a show, from finding and working out the initial idea, through to the ways in which writers can market a finished show and get it produced. For the interested theatregoer and writers, it is written in a lively and user-friendly style and illustrated with numerous examples.